Efektivitas Ekstrak Kulit Buah Limau Kuit (Citrus Amblycarpa) sebagai Larvasida Aedes Aegypti Instar III - Nuning Irnawulan Ishak; Kasman Kasman; Chandra Chandra (Media Kesehatan Masyarakat Indonesia, 2019)
Various negative effects from the use of chemical larvacides encourage research about natural larvacides,one of which is extract of lime skin extract. This study aimed to determine the effectiveness of lime skin extractas a natural larvacide against the death of Aedes aegypti larvae. This study uses a true experiment design with apost test only control group design. The object of the research was the lime peel extract. The sample size in thisstudy was 450 instar III larvae with Simple Random Sampling technique and treated with various concentrationsof lime skin extract (2ml/100ml, 3ml/100 ml, 4ml/100ml, and 5ml/100 ml) for 10 hours. Positive controls use abate0.01 gr / 100ml. The results showed that all treatment groups could kill 100% of larvae. At a concentration of 4.0ml / 100ml and 5.0 ml / 100ml experienced 100% mortality after 6 hours of measurement and the positive controlgroup experienced 100% death after 4 hours of measurement. The results of the probit analysis show that the valueof LT50 concentration of 5.0% is 2.58 hours and the value of LT99 is 5.86 hours. The Kruskal Wallis test resultsshowed no significant differences (p>0.05) larvae mean mortality between treatment groups and the control group.Giving skin extracts of lime juice can be a natural larvicidal alternative that can be used by the community.